Pengaruh Kepemimpinan Kepala Sekolah terhadap Motivasi Kerja Guru di MA Swasta Nururrodhiyah Kota Jambi - Jamaludin Jamaluddin; Dian Nisa Istofa; Bety Suremi (JMiE (Journal of Management in Education), 2021)
This research aims to find out the magnitude of the influence of the principal's leadership on the motivation of teacher work in the Private MA Nururrodhiyah Kota Jambi. This research is a quantitative study using correlational research design, while data analysis techniques use normality and product moment correlation tests. The results of this study found that the sample of principals in 20 teachers who were sampled obtained an average score of 70, a median of 72,625, a mode of 72 with a standard deviation of 13,265. While the results of teacher work motivation from the data obtained an average score of 77.8, median of 77.5, mode of 74.5, and standard deviation of 27.72. The product moment correlation test rxy = 0.976 is greater than rtabel so it is known that at the significance level of 5% = 0.444 and at the significance level of 1% = 0.561 then Ho was rejected and Ha accepted.